PENGARUH BRAND IMAGE, BRAND TRUST, KUALITAS PRODUK DAN INOVASI PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Wanita Pengguna Kosmetik Wardah Di Serdang Bedagai) - Bobby Hartanto (Jurnal AKTUAL, 2022)
This study aims to determine the effect of brand image, brand trust, product quality and product innovation on consumer satisfaction mediated by purchasing decisions for Wardah cosmetics in Serdang Bedagai. The effect that we want to know in this study is the direct and indirect effect. This type of research is explanatory research which explains the influence between variables in this study through hypothesis testing. The sample in this study were 96 respondents. The sampling technique used is accidental sampling. Data collection techniques by giving questionnaires to respondents. Statistical tests and data processing were carried out using Partial Least Square (SmartPLS 3.0). The results of this study are: Brand Image, Brand Trust, Product Quality have a significant effect on Purchase Decisions; and Product Innovation has no effect on Purchase Decisions; Purchase Decision has a significant effect on Consumer Satisfaction; Brand Trust and Product Quality have a significant effect on Consumer Satisfaction while Brand Image and Product Innovation have no effect on Consumer Satisfaction; There is a significant effect between Brand Image, Brand Trust, Product Quality on Consumer Satisfaction mediated by Purchase Decisions and there is no influence between Product Innovation on Consumer Satisfaction mediated by Purchase Decisions.